A note on truss topology optimization under self-weight load: mixed-integer second-order cone programming approach - Kanno, Yoshihiro; Yamada, Hiromichi (Structural and multidisciplinary optimization, 2017)
The self-weight load is a typical design-dependent load in structural optimization. This paper presents a mixed-integer second-order cone programming approach to global optimization of truss topology under the self-weight load.